Polyethyleneimine-grafted indium sulfide composite material containing rich sulfur vacancies as well as preparation method and application of polyethyleneimine-grafted indium sulfide composite material
By grafting polyethyleneimine onto indium sulfide containing abundant sulfur vacancies to form a composite material, the problems of low yield and high cost of indium sulfide catalysts in the photocatalytic production of hydrogen peroxide in the existing technology have been achieved. Efficient and economical hydrogen peroxide generation.
Patent Information
- Application Number
- CN202411883990.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-20
AI Technical Summary
In the prior art, indium sulfide catalysts containing sulfur vacancy have lower yields and higher costs when photocatalyzing the production of hydrogen peroxide (H2O2), and need to add artificial synthetic agents to increase production costs.
Develop a polyethylene amine (PEI) branches that are rich in sulfur (IN2S3-SV) composite materials that are rich in sulfur vacancy. The composite material is formed by electrostatic self-assembly method. Base, thereby increasing the generation rate of H2O2.
The efficient production of hydrogen peroxide has been achieved, which significantly improves the genetic rate of hydrogen peroxide of the catalyst, reduces production costs, and does not need to add an artificial synthetic agent, which has the advantages of sustainable and economic.
Smart Images

Figure CN119327515A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of indium sulfide catalyst materials, and in particular to a polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies, and a preparation method and application thereof. Background Art
[0002] As one of the most important green chemicals, hydrogen peroxide (H2O2) has been widely used in chemical synthesis, bleaching, food processing, biomedical treatment and environmental remediation, and is closely related to human life and industrial production. The current method of continuous production of H2O2 relies on the complex anthraquinone (AQ) process, involving energy-consuming multi-step hydrogenation and oxidation reactions, which runs counter to the concept of modern green chemistry. Photocatalytic H2O2 production (PHP) is a sustainable method that uses sunlight as an energy source to mimic photosynthesis and generate H2O2 from pure water and oxygen. The coupling of H2O and O2 to produce H2O2 is a sunlight-driven reaction (1 / 2O2 + H2O = H2O2, ΔG = 117 kJ mol -1 ). Currently, the concentration of commercial H2O2 is about 30-70wt%, while low-concentration H2O2 is usually used in practical applications. PHP runs entirely on solar energy and can produce low-concentration H2O2 solutions on-site using water and oxygen (air) as raw materials, thus avoiding the transportation and storage costs and safety hazards brought by high-concentration H2O2 solutions.
[0003] There are two possible pathways for the photocatalytic production of H2O2: (1) the two-electron oxygen reduction reaction (ORR, O2+ 2e − + 2H + = H2O2), which is the main pathway; (2) two-electron water oxidation reaction (2e − WOR)(2H2O + 2h + = H2O2 + 2H + The ORR can be further divided into a one-step two-electron reaction (O2+ 2e − + 2H + =H2O2) and two-step one-electron reaction (O2+ e − = •O2 − , •O2 − + e − + 2H + → H2O2). It is worth noting that in the process of photocatalytic synthesis of H2O2, most semiconductor materials, such as g-C3N4, TiO2 and CdS, will form intermediate active species •O2 − Although indium sulfide containing sulfur vacancies can produce a large amount of active species • O2 −, but its ability to produce hydrogen peroxide is relatively poor. One of the factors limiting the production of H2O2 is that the half-reaction (WOR) with slower kinetics is difficult to provide sufficient protons for the half-reaction (ORR) with faster kinetics. Most previous reports have focused on improving the half-reaction of O2 reduction, such as by using sacrificial agents such as isopropanol, benzyl alcohol, and 2-propanol to consume photogenerated holes while generating protons required for the ORR reaction. However, the addition of artificial synthetic agents not only increases the overall production cost, but also brings challenges in stripping by-products, limiting its subsequent application.
[0004] Based on the above background, if a method can be developed to further protonate and hydrogenate the superoxide radicals produced by indium sulfide containing sulfur vacancies, an excellent hydrogen peroxide yield will be obtained, and the cost of hydrogen peroxide production can be greatly reduced, which has great commercial prospects. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies, and a preparation method and application thereof.
[0006] The first object of the present invention is to provide a polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies, comprising indium sulfide containing abundant sulfur vacancies (In2S3-S V ), and polyethyleneimine (PEI) grafted on the indium sulfide containing rich sulfur vacancies; the Zeta potential of the surface of the indium sulfide containing rich sulfur vacancies is negative, and the Zeta potential of the surface of the polyethyleneimine is positive, and a composite material (PEI / In2S3-S V composite materials).
[0007] In some embodiments of the present invention, the grafting amount of the polyethyleneimine is 1 wt.%-5 wt.%.
[0008] In some embodiments of the present invention, the surface Zeta potential of the polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies is 40-45 mV.
[0009] The second object of the present invention is to provide a method for preparing the polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies, comprising the following steps: S1. dispersing the indium source in the sulfur-containing organic matter and heating it to obtain indium sulfide containing abundant sulfur vacancies; S2. Adding the obtained indium sulfide rich in sulfur vacancies to a polyethyleneimine solution, and heating to obtain the polyethyleneimine-grafted indium sulfide composite material rich in sulfur vacancies.
[0010] In some embodiments of the present invention, in S1, the indium source is selected from indium chloride and / or indium nitrate; The concentration of the indium source is 5-20 g / L; The molar ratio of the indium source to the sulfur-containing organic matter is (0.5-1.8):1.
[0011] In some embodiments of the present invention, in S1, the sulfur-containing organic compound is selected from thioacetamide and / or thiourea / L-cysteine; The heating temperature is 90-120° C., and the heating time is 12-36 h.
[0012] In some embodiments of the present invention, in S2, the heating temperature is 50-70°C, and the heating time is 6-48h.
[0013] In some embodiments of the present invention, in S2, the molecular weight of polyethyleneimine in the polyethyleneimine solution is 1800-10000; The mass concentration of the polyethyleneimine solution is 2.0-50%.
[0014] In some embodiments of the present invention, in S2, the mass ratio of the indium sulfide containing rich sulfur vacancies to the polyethyleneimine in the polyethyleneimine solution is (0.5-2):1.
[0015] The third object of the present invention is to provide the use of the polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies in a hydrogen peroxide production reaction.
[0016] In the present invention, PEI has excellent proton adsorption capacity and can quickly make In2S3-S V The generated superoxide radicals are rapidly hydrogenated and then converted into hydrogen peroxide. In addition, the protonated PEI surface has positive points, while the superoxide radicals have negative charges, so it is easier to desorb the superoxide radicals from the catalyst surface through electrostatic attraction, thereby forming free hydrogen peroxide to prevent the catalyst from decomposing the hydrogen peroxide generated in situ.
[0017] The above technical solution of the present invention has the following advantages compared with the prior art: (1) PEI / In2S3-S V The composite catalyst has an excellent hydrogen peroxide generation rate under actual catalytic reaction conditions; this is because the PEI / In2S3-S V The PEI molecules on the surface of the composite material can adsorb hydrogen protons in water, and then quickly adsorb and reduce superoxide radicals, significantly improving the activation efficiency of oxygen molecules.
[0018] (2) PEI / In2S3-S described in the present invention VThe composite catalyst has economic benefits and sustainable utilization; this is because the working conditions of the present invention do not require an organic sacrificial agent, and thus there is no need to deal with by-products derived from the organic sacrificial agent; secondly, the present invention can work in the visible light range (λ > 420 nm) without the need for additional energy input, and thus has considerable economic benefits and is environmentally friendly.
[0019] (3) PEI / In2S3-S described in the present invention V The composite catalyst has excellent long-term catalytic activity (the catalyst can still work after four hours) and recyclability (more than 80% of the catalytic activity is still maintained after three cycles). Even if the catalyst is deactivated, it can be restored by soaking in a diluted PEI solution. The operation is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein: Figure 1 PEI / In2S3-S in Example 1 of the present invention V X-ray diffraction patterns of composite materials; Figure 2 PEI / In2S3-S in Example 1 of the present invention V Surface Zeta potential diagram of the composite material and the material obtained in Comparative Example 1; Figure 3 PEI / In2S3-S in Example 1 of the present invention V DMPO-•O2 of composite materials − EPR spectrum of Figure 4 The photocatalytic production of hydrogen peroxide by different catalysts in the present invention; Figure 5 PEI / In2S3-S in Example 1 of the present invention V The H2O2 generation and decomposition rates of the composite material and the material obtained in Comparative Example 1; Figure 6 PEI / In2S3-S in Example 1 of the present invention V The composite material has long-term H2O2 production performance. DETAILED DESCRIPTION
[0021] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0022] Example 1
[0023] This embodiment provides a PEI / In2S3-S V Preparation methods and applications of composite materials.
[0024] 1. PEI / In2S3-S V Preparation method of composite material (1) 0.2212 g of anhydrous indium chloride and 0.0751 g of thioacetamide were added to a 100 ml polytetrafluoroethylene-lined hydrothermal reactor containing 35 ml of ultrapure water. After stirring for 30 minutes, the hydrothermal reactor was placed in an oven and heated to 90 °C at a heating rate of 10 °C / min for 12 h. After cooling to room temperature, the resulting orange suspension was collected, washed three times with distilled water and ethanol, and then dried overnight at 60 °C under vacuum to obtain an indium sulfide material containing abundant sulfur vacancies.
[0025] (2) 0.5 g of the indium sulfide material containing abundant sulfur vacancies obtained in step (1) was dispersed in an aqueous solution containing 20 ml of PEI, wherein the mass fraction of PEI (molecular weight of 10,000) was 2.4 wt%, and then stirred at 70°C at a stirring rate of 500 rmp for 12 h. After the reaction, the orange solid material was collected by centrifugation, washed three times with distilled water and ethanol, and then dried overnight under vacuum at 60°C to obtain a PEI-grafted indium sulfide material containing abundant sulfur vacancies, namely PEI / In2S3-S V Composite materials.
[0026] Example 2
[0027] This embodiment provides a PEI / In2S3-S V Preparation methods and applications of composite materials.
[0028] 1. PEI / In2S3-S V Preparation method of composite material (1) 0.2212 g of anhydrous indium nitrate and 0.0751 g of thioacetamide were added to a 100 ml polytetrafluoroethylene-lined hydrothermal reactor containing 35 ml of ultrapure water. After stirring for 30 minutes, the hydrothermal reactor was placed in an oven and heated to 100 °C at a heating rate of 10 °C / min for 15 h. After cooling to room temperature, the resulting orange suspension was collected, washed three times with distilled water and ethanol, and then dried overnight at 60 °C under vacuum conditions to obtain an indium sulfide material containing abundant sulfur vacancies.
[0029] (2) 0.5 g of the indium sulfide material containing abundant sulfur vacancies obtained in step (1) was dispersed in an aqueous solution containing 20 ml of PEI, wherein the mass fraction of PEI (molecular weight of 2500) was 15 wt%, and then stirred at 60°C at a stirring rate of 500 rmp for 20 h. After the reaction, the orange solid material was collected by centrifugation, washed three times with distilled water and ethanol, and then dried overnight at 60°C under vacuum conditions to obtain a PEI-grafted indium sulfide material containing abundant sulfur vacancies, namely PEI / In2S3-S V Composite materials.
[0030] Example 3
[0031] This embodiment provides a PEI / In2S3-S V Preparation methods and applications of composite materials.
[0032] 1. PEI / In2S3-S V Preparation method of composite material (1) 0.2212 g of anhydrous indium chloride and 0.0751 g of thioacetamide were added to a 100 ml polytetrafluoroethylene-lined hydrothermal reactor containing 35 ml of ultrapure water. After stirring for 30 minutes, the hydrothermal reactor was placed in an oven and heated to 90 °C at a heating rate of 10 °C / min for 12 h. After cooling to room temperature, the resulting orange suspension was collected, washed three times with distilled water and ethanol, and then dried overnight at 60 °C under vacuum to obtain an indium sulfide material containing abundant sulfur vacancies.
[0033] (2) 0.5 g of the indium sulfide material containing abundant sulfur vacancies obtained in step (1) was dispersed in an aqueous solution containing 20 ml of PEI, wherein the mass fraction of PEI (molecular weight of 5000) was 10 wt%, and then stirred at 70°C at a stirring rate of 500 rmp for 12 h. After the reaction, the orange solid material was collected by centrifugation, washed three times with distilled water and ethanol, and then dried overnight under vacuum at 60°C to obtain a PEI-grafted indium sulfide material containing abundant sulfur vacancies, namely PEI / In2S3-S V Composite materials.
[0034] Example 4
[0035] This embodiment provides a PEI / In2S3-S V Preparation methods and applications of composite materials.
[0036] 1. PEI / In2S3-S V Preparation method of composite material (1) 0.2212 g of anhydrous indium chloride and 0.0751 g of thioacetamide were added to a 100 ml polytetrafluoroethylene-lined hydrothermal reactor containing 35 ml of ultrapure water. After stirring for 30 minutes, the hydrothermal reactor was placed in an oven and heated to 120 °C at a heating rate of 10 °C / min for 12 h. After cooling to room temperature, the resulting orange suspension was collected, washed three times with distilled water and ethanol, and then dried overnight at 60 °C under vacuum to obtain an indium sulfide material containing abundant sulfur vacancies.
[0037] (2) 0.5 g of the indium sulfide material containing abundant sulfur vacancies obtained in step (1) was dispersed in an aqueous solution containing 20 ml of PEI, wherein the mass fraction of PEI (molecular weight of 3000) was 2.4 wt%, and then stirred at 50°C at a stirring rate of 500 rmp for 30 h. After the reaction, the orange solid material was collected by centrifugation, washed three times with distilled water and ethanol, and then dried overnight under vacuum at 60°C to obtain a PEI-grafted indium sulfide material containing abundant sulfur vacancies, namely PEI / In2S3-S V Composite materials.
[0038] Comparative Example 1 This comparative example uses In2S3-S containing abundant sulfur vacancies without PEI grafting. V The catalyst was used as a control.
[0039] 1. In2S3-S V Method for preparing catalyst 0.2212 g of anhydrous indium chloride and 0.0751 g of thioacetamide were added to a 100 ml polytetrafluoroethylene-lined hydrothermal reactor containing 35 ml of ultrapure water. After stirring for 30 minutes, the hydrothermal reactor was placed in an oven and heated to 90 °C at a heating rate of 10 °C / min for 12 h. After cooling to room temperature, the resulting orange suspension was collected, washed three times with distilled water and ethanol, and then dried overnight under vacuum at 60 °C to obtain an indium sulfide material (In2S3-S V ).
[0040] Structural characterization and performance testing (I) PEI / In2S3-S obtained in Example 1 V Composite material and In2S3-S obtained in Comparative Example 1 V The photocatalytic material was structurally characterized and the results are shown in Figure 1 and Figure 2 .
[0041] The PEI / In2S3-S obtained in this example V The X-ray diffraction pattern of the composite material is as follows Figure 1As shown in the figure, the composite materials obtained in Example 1 and Comparative Example 1 have good crystallinity and perfectly match the PDF of In2S3 (#32-0456). It also shows that the grafting of PEI does not destroy the In2S3-S V Crystal structure of PEI / In2S3-S V The surface Zeta potential characterization results of the composite materials, such as Figure 2 As shown, In2S3-S V The surface Zeta potential of PEI / In2S3-S is negative. When PEI with positive surface Zeta potential is grafted, the obtained PEI / In2S3-S V The surface Zeta potential of the composite material is positive, indicating that PEI is successfully grafted onto In2S3-S V Surface. In Comparative Example 1, In2S3-S V The surface Zeta potential characterization results of photocatalytic materials are as follows Figure 2 As shown, In2S3-S V The surface Zeta potential of In2S3-S is -28.28, indicating that V It can be combined with PEI with positive surface Zeta potential through electrostatic self-assembly.
[0042] In addition, the surface positive Zeta potential of PEI / In2S3-S V The composite material can also adsorb superoxide radicals • O2 generated in situ by photocatalysis through electrostatic attraction. − , which is further converted into H2O2. The EPR technique using DMPO as a spin trap also revealed that PEI / In2S3-S V •O2 in composite materials systems − Intermediate, the result is Figure 3 As shown. In the absence of light, PEI / In2S3-S V No DMPO-•O2 was detected in the material system − characteristic peak, indicating that the system does not produce •O2 in the absence of light − After 5 minutes of light exposure, PEI / In2S3-S V The material system showed obvious DMPO-•O2 − The characteristic peak of the intermediate product proves that H2O2 in the system is produced by two-step single electron transfer. The stable concentration of photocatalytic H2O2 is determined by the photocatalytic H2O2 production and H2O2 decomposition capabilities of the material. V The photocatalytic H2O2 production and decomposition performance of the composite material are shown in the following table. Figure 5 As shown in the figure, the PEI / In2S3-S VThe composite material has an excellent H2O2 production rate (3.57 μM min -1 ), In2S3-S in Comparative Example 1 V The photocatalytic material has a slow rate of H2O2 production (0.22 μM min -1 ), and a faster decomposition rate of H2O2 (0.0187 min -1 ), so In2S3-S V The photocatalytic performance of producing hydrogen peroxide is relatively poor. It can be seen that the rate of producing H2O2 by the material obtained in Example 1 of the present invention is much higher than that of In2S3-S in Comparative Example 1. V The rate of H2O2 production. In addition, PEI / In2S3-S V The composite material decomposes H2O2 at a slower rate (0.0034min -1 ), which is much lower than that of In2S3-S in Comparative Example 1 V The rate of decomposition of H2O2 (0.0187 min -1 ). In summary, PEI / In2S3-S V The excellent H2O2 generation performance of the composite material is attributed to the excellent H2O2 production performance and poor H2O2 decomposition performance. V Catalyst stability test diagram of composite materials ( Figure 4 ), the test conditions are the same as those of the hydrogen peroxide reaction experiment. The figure shows that PEI / In2S3-S V The composite material has good catalytic reaction stability.
[0043] (II) Photocatalytic H2O2 production experiment 30 mg of the prepared PEI / In2S3-S V The composite photocatalyst was dispersed in 30 ml of deionized water (catalyst concentration was 1 g L -1 ) in a 50 ml quartz reactor. Before the reaction, the catalyst was dispersed by ultrasound for 5 minutes. Subsequently, the reaction system was irradiated with a 300 W xenon lamp (PCX50C, Beijing Perfect Light Source Technology Co., Ltd.) equipped with a 420 nm cutoff filter at room temperature. The concentration of H2O2 generated was analyzed by iodine titration. Typically, 0.5 ml of 0.4 M potassium iodide (KI, purity ≥99%, Aladdin) aqueous solution and 0.5 ml of 0.1 M potassium hydrogen phthalate (purity ≥99.5%, Aladdin) aqueous solution were added to 1 ml of the aqueous phase product and kept for 30 minutes. The absorbance of the mixed solution at a wavelength of 350 nm was then detected by UV-visible spectroscopy, from which the amount of H2O2 generated was estimated. The following reactions occurred in the mixed solution: The generated I3 −The light absorption peak appears around 350 nm. H2O2+ 3I − + 2H + = I3 − + 2H2O Figure 4 PEI / In2S3-S obtained in Example 1 V The catalyst stability test diagram of the composite material shows that PEI / In2S3-S V Excellent H2O2 production rate (194 μM h -1 ), is a comparative example of In2S3-S V The experimental data show that PEI / In2S3-S V The composite material has the feasibility of photocatalytically producing H2O2. Compared with Example 1, the In2S3-S V The photocatalyst material showed a lower photocatalytic H2O2 production performance of only 8 μM h -1 .
[0044] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies, characterized in that: The invention comprises indium sulfide containing rich sulfur vacancies and polyethyleneimine grafted on the indium sulfide containing rich sulfur vacancies; the Zeta potential on the surface of the indium sulfide containing rich sulfur vacancies is negative, and the Zeta potential on the surface of the polyethyleneimine is positive, and a composite material is formed by an electrostatic self-assembly method.
2. The polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies according to claim 1, characterized in that: The grafting amount of the polyethyleneimine is 1 wt.%-5 wt.%.
3. The polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies according to claim 1, characterized in that: The surface Zeta potential of the polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies is 40-45 mV.
4. A method for preparing a polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies as claimed in any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Dispersing the indium source in sulfur-containing organic matter and heating it to obtain indium sulfide containing abundant sulfur vacancies; S2. Adding the obtained indium sulfide rich in sulfur vacancies to a polyethyleneimine solution, and heating to obtain the polyethyleneimine-grafted indium sulfide composite material rich in sulfur vacancies.
5. The preparation method according to claim 4, characterized in that: In S1, the indium source is selected from indium chloride and / or indium nitrate; The concentration of the indium source is 5-20 g / L; The molar ratio of the indium source to the sulfur-containing organic matter is (0.5-1.8):
1.
6. The preparation method according to claim 4, characterized in that: In S1, the sulfur-containing organic matter is selected from thioacetamide and / or thiourea / L-cysteine; The heating temperature is 90-120° C., and the heating time is 12-36 h.
7. The preparation method according to claim 4, characterized in that: In S2, the heating temperature is 50-70°C, and the heating time is 6-48h.
8. The preparation method according to claim 4, characterized in that: In S2, the molecular weight of polyethyleneimine in the polyethyleneimine solution is 1800-10000; The mass concentration of the polyethyleneimine solution is 2.0-50%.
9. The preparation method according to claim 4, characterized in that: The mass ratio of the indium sulfide containing abundant sulfur vacancies to the polyethyleneimine in the polyethyleneimine solution is (0.5-2):
1.
10. Use of the polyethyleneimine-grafted indium sulfide composite material containing abundant sulfur vacancies according to any one of claims 1 to 3 in a hydrogen peroxide production reaction.
Citation Information
Patent Citations
Preparation method and application of indium sulfide / hydrothermal carbon composite photocatalyst
CN118122345A
Process for preparing H2O2
DE3538816A1
3D reduced graphene oxide foams embedded with nanocatalysts, synthesizing methods and applications of same
US20190048482A1
Cited By
Preparation method and application of indium sulfide photocatalytic material with specific vacancy
CN120662337A